2020
DOI: 10.1177/0192623320946705
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Immunomodulatory Drugs and Infection in the Respiratory Tract of Nonhuman Primates

Abstract: Though rare due to measures and practices to control the risk, infections can occur in research and toxicology studies, especially in nonhuman primates (NHPs) exposed to xenobiotics, particularly immunomodulatory drugs. With such xenobiotics, immunocompromised or immunosuppressed animals will not be able to mount a protective response to infection by an opportunistic pathogen (bacteria, virus, parasite, or fungus) that might otherwise be nonpathogenic and remain clinically asymptomatic in immunocompetent anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…While many procedural factors predispose to lung infection such as aspiration (during gavage studies) and BAL collection, test article pharmacology should always be considered, especially if the drug is an immunomodulator, as it may reduce immunological function through immunosuppression. To help readers in this regard, Flandre et al 7 review the most common opportunistic infections observed in the respiratory tract of NHPs and discuss how they might impact the interpretation of pathology findings.…”
mentioning
confidence: 99%
“…While many procedural factors predispose to lung infection such as aspiration (during gavage studies) and BAL collection, test article pharmacology should always be considered, especially if the drug is an immunomodulator, as it may reduce immunological function through immunosuppression. To help readers in this regard, Flandre et al 7 review the most common opportunistic infections observed in the respiratory tract of NHPs and discuss how they might impact the interpretation of pathology findings.…”
mentioning
confidence: 99%